Grooved Building Blocks for Concealed Utility Services - Solanki, Rakesh Kumar; Ansari, A. A.; Aravind Kumar, A. (AMC Indian Journal of Civil Engineering, 2020)
The article presents novel innovative design and development of grooved building blocks for concealed mechanical, electrical, and plumbing (MEP) utility services installations. These grooved blocks design is useful for concealing electrical wiring, water pipeline, and route for drain water required for different utility services on wall and floor. A wall prototype model constructed with grooved blocks of different designs such as straight horizontal, vertical, multi-way junction box, bend shape, and L-shape cut bricks with MEP system utility services installations. Comparative evaluation of the traditional concealed systems with grooved blocks were carried out. The grooved building blocks of the present invention was economical, reduces manpower, and time for concealed utility services.